Learning in organizations : an evidence-based approach - Ford, J. Kevin 1954- (Routledge, Taylor & Francis Group, 2021)
Learning in Organizations: An Evidence-Based Approach examines the variety of systematic approaches and strategies for learning and development used in the workplace through the implementation of formal training, guided instruction, developmental job experiences, and self-directed learning. The hallmark of Learning in Organizations is an emphasis on research evidence of what is and is not known about learning and learning strategies and the translation of that evidence to guide best practices in workplace learning and development. The book features evidence on learning principles, new learning technologies, and strategies for developing individual, team, and leadership capabilities. The content of the chapters is enhanced by the inclusion of key learning goals for each chapter, case studies, chapter summaries, best practice recommendations, and a hands-on project for use in the classroom. Learning in Organizations provides researchers with a detailed investigation of learning practices to help drive future research. For learning practitioners, research evidence is translated into best practices that can be applied to enhance workplace learning and development. For undergraduate and graduate students, the book provides an up-to-date review of the key concepts and ways of thinking about and studying learning in the workplace.